Pengembangan Kurikulum bagi Siswa Berkebutuhan Khusus di SMK Negeri 4 Padang dalam Setting Pendidikan Inklusif - Asep Ahmad Sopandi (Pedagogi: Jurnal Ilmu Pendidikan, 2013)
The research is motivated by problems that arise in Sekolah Menengah Kejuruan (SMK) Negeri 4, that the development of a curriculum do not accommodate all students, especially students with special needs in accordance with the procedure or provision contained in filosopi inclusive education. This research aims to describe the development of school curricula do inclusive education in SMK Negeri 4 Padang. To achieve the research objectives, we used a qualitative approach with a qualitative descriptive method. While the data collection techniques and tools, namely interviews using an interview guide and observation techniques using observation and study engineering documentation. Subjects consisted of teachers who teach subjects in the classroom of students with special needs, inclusive education managers, and students with special needs themselves. These results explained that the development of curriculum that the teachers do not differ with the previous curriculum development, standard analytical procedures and basic competencies, mapping of materials, methods, media and evaluation of learning outcomes.